The Effects of Human Activities on Amazon Rain Forest - Tilahun, Zewde Alemaheyehu (International Journal of Scientific Research in Civil Engineering, 2024)
The huge diversity of tree species found in the Amazon rainforest presents both an opportunity and a problem for the exploitation of non-timber products. Overall, progress towards the sustainable forest management was mixed in South America. The diversity offers vast arrays of potential harvestable crops are sparsely distributed. There are some of the timbers three species (such as the Brazil nut and rubber) found in the Amazon rainforest, which are producing non-timber products that can be harvested while the timber is maturing. It is not the most species-diverse forests which have the most potential for non-timber products; in certain areas under adverse environments, such as swamp forests and transition forests where there is a dominance of one or a few species; there is considerable opportunity to use non-timber products. The single most important plant family for such products is the palms, which often dominate the species-poor habitats. However, there are many other plant species from the species-diverse forest with potential for domestication; a number of these are described in this paper. However, recent anthropological findings have suggested that the region was actually densely populated. Some 5 million people may have lived in the Amazon region in AD 1500, divided between dense coastal settlements, such as that at Marajo, and inland dwellers.[17] By 1900 the population had fallen to 1 million and by the early 1980s it was less than 200,000 The first European to travel the length of the Amazon River was Francisco de Orellana in 1542. The BBC’s Unnatural Histories presents evidence that Orellana, rather than exaggerating his claims as previously thought, was correct in his observations that a complex civilization was flourishing along the Amazon in the 1540s. It is believed that the civilization was later devastated by the spread of diseases from Europe, such as smallpox.[19] Since the 1970s, numerous Geoglyphs have been discovered on deforested land dating between AD 0–1250, furthering claims about Pre-Columbian civilizations. Ondemar Dias is accredited with first discovering the Geoglyphs in 1977 and Alceu Ranzi with furthering their discovery after flying over Acre. The BBC’s Unnatural Histories presented evidence that the Amazon rainforest, rather than being a pristine wilderness, has been shaped by man for at least.